Medical Occupational Health Services Needs of Women Academics in Benue State: Implications for Health Promotion - Burbwa, Sarah; Samuel, E. S. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
The study investigated the medical occupational health services needs (MOHSNs) of university women academics in Benue State with the view to proffer suggestions on the provision of basic medical occupational health services needs for health promotion and effective job performance. The study utililized the cross-sectional research design. The population of the study consisted of all university women academics, and two key officers involved in the provision of MOHS in the state and federal government owned universities in Benue state. A sample size of two hundred and ninety-eight (298) participants comprising 296 university women academics and two key officers participated in the study .Three instruments were used for data collection. These were an 11-item adapted and modified community needs assessment questionnaire by Aparna, Mindy and Yolanda (2000), otherwise called Medical Occupational Health Services Needs Assessment Questionnaire (MOHSNAQ). A Focus Group Discussion (FGD) guide, and Key Information Interview (KII) guide structured by the researchers were validated and utilized for data collection. The reliability co-efficient index of OHSNAQ was determined through split half method which yield reliability co-efficient index of .90 for section A, and .84 for section B as determined through Cronbach Alpha statistic. Data collected were analysed using mean, percentages, chi-Square statistics. The findings indicated that MOHSNs of women academics were: follow-up medical care services 69.30%, rehabilitation services 68.10%, eye care services 63.50%, gynaecological health care services 58%, and health counseling services 54.50% .Results further showed that there were no significant differences in the MOHSNs of the women academics based on Age (Calχ2value = 1.813, P= .430 > 0.05).The study concludes that women academics have medical services needs. It is recommended that, the universities should design strategies for the provision of the needed MOHS.